Laparoscopic adrenalectomies: A nationwide single-surgeon experience - Bjornsson, Bergthor; Birgisson, Gudjon; Oddsdottir, Margret (Surgical Endoscopy, 2008)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: Laparoscopic adrenalectomy (LA) was first performed in Iceland in 1997. Since then, all procedures for presumed benign lesions of the adrenals have been performed laparoscopically in a single center. Compared with conventional adrenalectomy, LA appears to achieve superior results in terms of recovery, hospital stay, and morbidity. This study aimed to evaluate the results of LA in Iceland. METHODS: The hospital records of all patients who underwent LA in Iceland from 1997 through 2005 were reviewed. The preoperative diagnosis was documented, as well as the pathologic diagnosis, operative details, complications, and length of hospital stay. RESULTS: In 49 operations, 53 adrenal glands were removed from 48 patients (37 women and 11 men). The mean patient age was 53.6 years (range, 24.4-78.8 years). The left adrenal was removed from 29 patients, the right adrenal from 14 patients, and both adrenals from 5 patients. The most common indications and diagnoses included 17 nonsecreting tumors (12 adenomas, 3 hyperplasias, 1 complex adrenal cyst, and 1 hemangioma), 12 aldosteronomas (10 aldosteronomas and 2 nodular hyperplasias), and 10 pheochromocytomas (9 confirmed, 1 adrenal hyperplasia). Other indications and diagnoses were less common. The mean operative time was 168 min (range, 87-370 min) for unilateral operations and 412 min (range, 345-480 min) for bilateral operations. The mean blood loss was 117 ml (range, 0-650 ml) for unilateral operations and 200 ml (range, 0-350 ml) for bilateral operations. The complications were mild pancreatitis (n = 1), urinary tract infection (n = 1), atelectasis (n = 1), mild congestive heart failure (n = 2), and transient corneal abrasion (n = 1). No conversion to open procedure was needed. The mean tumor size was 3.5 cm (range, 1.5-6.2 cm), and the mean postoperative hospital stay was 2.6 days (range, 1-6 days). CONCLUSION: The results of laparoscopic ...